2011
DOI: 10.4240/wjgs.v3.i11.167
|View full text |Cite
|
Sign up to set email alerts
|

Current status and recent advances of liver transplantation from donation after cardiac death

Abstract: The last decade saw increased organ donation activity from donors after cardiac death (DCD). This contributed to a significant proportion of transplant activity. Despite certain drawbacks, liver transplantation from DCD donors continues to supplement the donor pool on the backdrop of a severe organ shortage. Understanding the pathophysiology has provided the basis for modulation of DCD organs that has been proven to be effective outside liver transplantation but remains experimental in liver transplantation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Of these, two major predictors for graft loss were receiving a liver transplant due to the hepatitis C virus and receiving the liver organ from a nonheart‐beating donor. Both of these factors have previously been reported to have an association with graft loss . However, presence of DM in the donor was also found to independently predict graft loss in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Of these, two major predictors for graft loss were receiving a liver transplant due to the hepatitis C virus and receiving the liver organ from a nonheart‐beating donor. Both of these factors have previously been reported to have an association with graft loss . However, presence of DM in the donor was also found to independently predict graft loss in our study.…”
Section: Discussionmentioning
confidence: 72%
“…In 2000, type V was included, in which the critical patient's heart stops unexpectedly; this type was also categorized as uncontrolled DCD. ( 2 , 7 - 9 ) Table 1 shows the different categories of this classification system.…”
Section: Introductionmentioning
confidence: 99%
“…11 Subsequent work investigating this degree of graft failure suggested that DCD livers are injured by prolonged warm ischemic time due to the donation process, are more susceptible to postmortem clot formation, and have greater ischemic insult when compared to DBD donor grafts. 12 Further meta-analyses have suggested that DCD liver transplant recipients are also at a higher risk of developing ischemic cholangiopathy, further increasing the risk of graft failure and need for retransplantation. 13 Despite these complications, DCD livers provide otherwise unavailable organs and have been shown to reduce wait-list mortality and provide a definite survival benefit in patients with a high acuity of illness.…”
Section: Discussionmentioning
confidence: 99%